ОЦЕНКА ГОДНОСТИ ОБОРУДОВАНИЯ ЛОКОМОТИВОВ ПРИ ДОСТИЖЕНИИ ПОСЛЕ НОРМАТИВНОГО СРОКА ЭКСПЛУАТАЦИИ - Александр Семёнович Крашенинин; Елена Александровна Шапатина; Сергей Сергеевич Яковлев (World Science, 2019)
The article is devoted to the study of the assessment of the suitability of equipment locomotives in the the period after the end of the norms of operation based on the provisions of the theory of aging. It was determined that according to the minimization of the loss function of the axis of underutilization of equipment resources of locomotives, it is possible to extend their operation within 7–10 years, provided that this period is clarified for each specific equipment by the criterion of shelf life. This will give the opportunity to form the technology of Technical Service and Technical Regulations of equipment of locomotives after exceeding the standard lifetime.